Analysis of Demand and Supply of Radiotherapy Services at Dr.M.Djamil General Hospital Padang - Dewi, Viola Shinta; Suharinto, Catur; Zamzahar, Zarni; Yulhaini, Yulhaini (citeus, 2025)
Around 10 million cases of cancer are discovered in the world per year, and it will continue to increase. Half of cancer cases require radiotherapy as treatment therapy. Dr. M. Djamil General Hospital, Padang, in 2021, has only 1 Cobalt radiotherapy. This study aimed to analyze the demand and supply of radiotherapy services at Dr. M. Djamil General Hospital, Padang. This descriptive study was conducted at Dr. M. Djamil General Hospital, Padang from May to December 2022. Data were analyzed using univariate analysis to describe the variables studied. This study reported that 241 patients were registered and received radiotherapy services. The stages of radiotherapy are consultation, simulator, molding, TPS, and radiation. In the irradiation stage with Cobalt, an average of 25 minutes per irradiation was carried out, and on average, each patient underwent 18 irradiations. Based on the data, the estimated demand cannot yet be met due to the availability of tools and other obstacles. Irradiation with LINAC is more effective and efficient in terms of cost and time. It is hoped that the hospital can plan tools to optimize radiotherapy services at Dr. M. Djamil General Hospital, Padang.